Developing Children's Cognitive Ability In Numerating Objects At At-Tibyan Kindergarten, Banjarmasin, Indonesia - Noor Halida Yanti; Nurilla Santi; Rizki Nugerahani Elise (Universitas muhammadiyah Banjarmasin, 2021)
Study used a classroom action research design and was carried out in 4 meetings. The subjects of this study were group B children at Al-Badariyah Kindergarten, Banjarmasin City, totaling 13 children. The type of research data used is qualitative data. The assessment instrument used is an observation sheet for teacher and child activities taken during the learning process. Descriptive qualitative data analysis in the form of tables, graphs and interpretations using presentations. The indicators of the success of this research are the teacher's activities get a score of 30 in the